Performing the Cold War in the Postcolonial World : Theatre, Film, Literature and Things. - Balme, Christopher B. (Routledge Studies in Cultures of the Global Cold War Series, 2023)
This volume explores how the Cultural Cold War played out in Africa and Asia in the context of decolonization. Both the USA and the Soviet Union as well as East European states undertook significant efforts to influence cultural life in the newly independent, postcolonial world.